Jawahar Rojgar Yojana - A Quick Study 1991-92 - Planning Commission (Planning Commission, 1991)
The Jawahar Rozgar Yojana (JRY), launched in 1989, aimed to provide wage employment and improve rural infrastructure by merging the NREP and RLEGP schemes. An evaluation conducted in 1991 across ten high-poverty states revealed limited employment impact, with only 14% of eligible rural poor receiving jobs, averaging 13 days annually. While assets such as roads, wells, and schools were created, 56% were rated average or poor, and maintenance was largely inadequate. Implementation challenges included administrative inefficiencies, delayed fund disbursements, unrealistic wage-material ratios, and overreliance on contractors. The study recommends improving data collection, training Panchayat leaders, enhancing community participation, providing technical guidance, and ensuring timely financial releases. Addressing these shortcomings is critical to increasing JRY’s effectiveness in employment generation and sustainable rural asset development.
Programme Evaluation Organisation Planning Commission (Government of India) New Delhi
Programme Evaluation Organisation Planning Commission (Government of India) New Delhi
Keywords: Jawahar Rozgar Yojana; Rural Employment; Asset Creation; Gram Panchayats; Poverty Alleviation; Employment Generation; Asset Maintenance; Implementation Challenges; Community Participation; Financial Management; Technical Guidance; Programme Evaluation